The adventures of young H.C. Andersen and the brothers Grimm - Rybka, Jan; Capezzone, Thierry (Chicago, Illinois : World Book, 2020)
"In this adventure, H.C. is joined by a set of famed German storytellers$1 (Band a magical hat of their own! He does not meet creepy twins, but there are some grim brothers."--Cover.s
Keywords: Andersen, H. C. (Hans Christian), -- 1805-1875 -- Childhood and youth -- Comic books, strips, etc; Imagination -- Juvenile fiction -- Comic books, strips, etc